A Cautious Alliance: The Psychobiographer's Relationship with Her/His Subject. (27th August 2018) - Ponterotto, Joseph G.; Moncayo, Kevin
Abstract: Psychobiography has been a topical area and an applied research specialty in psychology since Freud's (1910/1989) influential psychoanalytic psychobiography of Leonardo da Vinci. Throughout the last century, psychobiographers have emphasized the importance of anchoring interpretations of life histories in established psychological theories and rigorous historiographic research methods. One topical area receiving less attention in psychobiography is the critical relationship between the psychobiographer and her or his subject as it relates to the process of psychobiographical writing. The present article explores the phenomenology and challenges of this relationship in order to ultimately propose practical strategies for navigating countertransference issues throughout the subject selection, research and publication phases of psychobiography. Freud's psychobiography of Leonardo da Vinci is used as a model of the stages of psychobiography, the evolution of the psychobiographer-subject relationship, and the challenges of countertransference.